THE ANALYSIS OF SEXIST LANGUAGE IN THE QUEEN’S GAMBIT DRAMA SERIES - Anak Agung Sandra Novita Dewi; Agus Darma Yoga Pratama (Center of Language and Cultural Studies, 2023)
This research aimed to find out types of overt sexism and indirect sexism as well as analyze the context of the situation on the data found in the drama series The Queen's Gambit which totals seven episodes. The data were in the form of words, phrases, and sentences from the drama series transcripts. This research used the theory of types of sexism by Mills (2008) and the theory of context of the situation by Hymes (1977). This research used a descriptive qualitative method and a non-participant observation method to analyze the data. In the data collection, this research used the transcript from each episode of the drama series to examine the data. The next step is watching the drama series The Queen's Gambit to find out the situation from the data obtained in the transcript. Then, this research identified, coded, classified, and analyzed the data that has been obtained. As a result, 70 data were observed, with 32 data on the type of overt sexism and 38 data on the type of indirect sexism and the most frequently occurring data is presupposition with a total amount of 14 data has been found.